2013
DOI: 10.1063/1.4809542
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical crack growth in SiNx thin-film barriers studied by electro-mechanical two-point bending

Abstract: Mechanical failure resulting from subcritical crack growth in the SiNx inorganic barrier layer applied on a flexible multilayer structure was studied by an electro-mechanical two-point bending method. A 10 nm conducting tin-doped indium oxide layer was sputtered as an electrical probe to monitor the subcritical crack growth in the 150 nm dielectric SiNx layer carried by a polyethylene naphthalate substrate. In the electro-mechanical two-point bending test, dynamic and static loads were applied to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
(35 reference statements)
3
19
0
Order By: Relevance
“…As the strain rate is increased above 0.01%·s –1 , ε c becomes independent of the environment. The effect of strain rate on ε c is consistent with the study by Guan et al., and the effect of humidity on time-dependent crack growth is consistent with the study by Vellinga et al Both studies demonstrated environmentally assisted cracking of the SiN x coatings on PEN polymers. Here, the crack growth rates and behavior were further characterized as a function of applied strains (from 0.6% to 0.85%)/driving forces (see numerical model in Figure c for corresponding G ss ), in different environments (laboratory air, dry nitrogen, dry air).…”
Section: Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As the strain rate is increased above 0.01%·s –1 , ε c becomes independent of the environment. The effect of strain rate on ε c is consistent with the study by Guan et al., and the effect of humidity on time-dependent crack growth is consistent with the study by Vellinga et al Both studies demonstrated environmentally assisted cracking of the SiN x coatings on PEN polymers. Here, the crack growth rates and behavior were further characterized as a function of applied strains (from 0.6% to 0.85%)/driving forces (see numerical model in Figure c for corresponding G ss ), in different environments (laboratory air, dry nitrogen, dry air).…”
Section: Results and Discussionsupporting
confidence: 88%
“…They argued that this environmental effect was unlikely due to the hygroscopic expansion of the polymer, and instead concluded that SiN x barriers undergo environmentally assisted cracking. Guan et al also performed electromechanical two-point bending tests in dynamic and static loading modes to determine the subcritical crack growth exponent n in SiN x coatings on PEN substrates. Their results suggest that SiN x thin films behaves differently from bulk Si 3 N 4 ceramics that are essentially immune to environmentally assisted cracking. , However, these studies neither directly measured the crack growth rates as a function of driving force for channel cracking nor considered the aforementioned potential effects of polymer relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…32 Guan et al have indicated that cracks may form in oxides at relatively low mechanical strains due to their brittle nature. 33 For the case of crack formation in the function layer, the resistance may increase upto a specic level and then lead to the initiation of the nal failure. 33,34 Chung et al have shown that the resistive switching of the Al/GeO 2 : S/Au device can withstand a tensile or compressive strain of up to 1.2%.…”
Section: Methodsmentioning
confidence: 99%
“…33 For the case of crack formation in the function layer, the resistance may increase upto a specic level and then lead to the initiation of the nal failure. 33,34 Chung et al have shown that the resistive switching of the Al/GeO 2 : S/Au device can withstand a tensile or compressive strain of up to 1.2%. 35 Shang et al have reported that cracks appear in the ITO/HfO x /ITO lm coated on the PET substrate when the mechanical tensile stress is up to 1.59%.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, a great deal of research has been dedicated to the study of the mechanical failure of brittle thin films on a polymer substrate [4][5][6][7][8][9][10][11][12][13][14][15][16]. Three main techniques have been widely used to analyze the mechanical properties of thin brittle, hard films on soft substrates, namely nanoindentation and the related scratch test [17,18], the tensile fragmentation test [16,11], and the electro-mechanical two-point bending test (which, more properly would be addressed as the two-plate bending test (2PB), as we will do in the current paper) [6,16]. Among these methods the fragmentation test, which enables a direct observation of the failure process and thus an accurate determination of failure mechanism in brittle thin films, is the most commonly used one.…”
Section: Introductionmentioning
confidence: 99%